2016
DOI: 10.1007/s13253-016-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimability Analysis and Optimal Design in Dynamic Multi-scale Models of Cardiac Electrophysiology

Abstract: We present an applied approach to optimal experimental design and estimability analysis for mechanistic models of cardiac electrophysiology, by extending and improving on existing computational and graphical methods. These models are ‘multi-scale’ in the sense that the modeled phenomena occur over multiple spatio-temporal scales (e.g., single cell vs. whole heart). As a consequence, empirical observations of multi-scale phenomena often require multiple distinct experimental procedures. We discuss the use of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…UQ helped to identify challenges concerning model calibration and parameter identification that will inform future model development. Such issues are frequently encountered in models of cardiac electrophysiology but are not often addressed during model development (Fink and Noble, 2009 ; Shotwell and Gray, 2016 ). In the Li et al ( 2017 ) I Kr Markov model, drug-hERG binding kinetics was characterized by six parameters, but one parameter (drug trapping rate, K t ) was fixed at a value of 3.5× 10 −5 ms −1 .…”
Section: Discussionmentioning
confidence: 99%
“…UQ helped to identify challenges concerning model calibration and parameter identification that will inform future model development. Such issues are frequently encountered in models of cardiac electrophysiology but are not often addressed during model development (Fink and Noble, 2009 ; Shotwell and Gray, 2016 ). In the Li et al ( 2017 ) I Kr Markov model, drug-hERG binding kinetics was characterized by six parameters, but one parameter (drug trapping rate, K t ) was fixed at a value of 3.5× 10 −5 ms −1 .…”
Section: Discussionmentioning
confidence: 99%
“…It is parsimonious because it was constructed was constructed to reproduce the specific set of experimental data sets (Figs 1 – 3 ) that capture important electrophysiological behavior with as few parameters as possible. In addition, we have recently shown that this model is mathematically identifiable (i.e., not over parameterized)[ 45 ]. Incidentally, as described by Biktashev et al [ 46 ] FitzHugh–Nagumo models fail to reproduce some features of cardiac ionic models such as: slow repolarization, slow sub-threshold response, non-Tikhonov asymptotic properties of excitability [ 47 ], wave front dissipation [ 48 ], and different action potential amplitude in single cells versus propagation [ 9 ] which our model captures (see Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…in multi-scale models and highlighted the need to use observations across multiple scales. Shotwell and Gray (2016) analyzed the problems caused by the use of observations across multiple scales and how to characterize the relationships between the model parameters and the effect that they have in the multi-scale model outputs.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%